IMPLEMENTASI PENDEKATAN RELIGIUS DALAM REHABILITASI KORBAN PENYALAHGUNAAN NARKOBA DI RUMAH SAKIT KHUSUS JIWA H. MUSTAJABAH PURBALINGGA - Mohammad Irfangi (Institut Agama Islam Negeri Purwokerto, 2017)
This paper aims to describe the rehabilitation of victims of drug abuse in the H.Mustajabah Special Hospital Mental Purbalingga. Drug abuse has become widespread in the community, for it required no special approach to medical and non-medical in handling by the stakeholders of government agencies, non-governmental, and private sectors. This was in line with the current development paradigm in which the three main pillars play an important role in the development process. This article utilizes literature studies, interviews, documentation and observation as a means to get information about how to implement a holistic approach in the rehabilitation of victims of drug abuse in the H.Mustajabah Special Hospital Mental Purbalingga. The results of the study concluded that the handling of victims of drug abuse in the H.Mustajabah Special Hospital Mental Purbalingga by promoting the Islamic religious aspect that comes from al-Qur'an, al-Sunna. Spiritual approach Islamic way is referred to as